Eco-innovation Implementation Framework For Malaysian Contracting Firms - Isa, Siti Sarah Mat (2023)
The construction industry is expected to excel in innovation while at the same time care for the environment, which makes the concept of eco-innovation (EI) an important direction for firms and the industry. Nonetheless, this application is still lagging compared to other industries. This research focuses on developing EI implementation framework by adapting the Dynamic Capability Theory. With 5 objectives to be achieved, a mixed method (QUAN-QUAL) comprising a questionnaire survey and semi-structured interview was employed. The data for this study was obtained from G7 contractor firms registered with the Construction Industry Development Board (CIDB). Based on the results of 103 survey responses and 14 interviews, it was discovered that there are 10 components of EI relevant to contractor firms that can be parked under process, product and organisational EI (Objective 1); the level of EI adoption remained moderate (Objective 2); the contractor firms are mainly driven by environment, technology, market, and firm-specific factors (Objective 3); there are 6 main challenges and 2 main supporting factors that influence EI implementation (Objective 4); and lastly, there are 4 key strategies (staff enrichment, technology optimisation, strengthen networking, and firm management proactiveness) to implement EI (Objective 5). The qualitative study validates the crucial connection of EI components and the influencing factors of EI implementation with EI strategy, enabling the development of the EI implementation framework. This framework facilitates the contracting firms to be more attentive in EI endeavour by providing a clear and comprehensive understanding of EI implementation to ensure continuous commitment to sustainable competitive advantages and environmental sustainability